Big data analytics for investigating Taiwan Line sticker social media marketing. Issue 2 (24th October 2019) - Liao, Shu-Hsien; Hsu, Szu-Yu
Abstract : Purpose: Line sticker, a social media, it allows users to exchange multimedia files and engage in one-to-one and one-to-many communication with text, pictures, animation and sound. The purpose of this paper is to examine various Taiwan user experiences in the Line sticker use behaviors. Further, this research looks at how the situations of Line sticker proprietors and their affiliates are disseminated for formulating social media marketing (SMM) in its business model concerns. Design/methodology/approach: This study examines the experience of various Taiwanese Line stickers users utilizing a market survey, a total of 1, 164 valid questionnaire data, and the questionnaire is divided into five sections with 30 items in terms of the database design. All questions use nominal and order scales. This study develops a big data analytics approach, including cluster analysis and association rules, based on a big data structure and a relational database. Findings: The authors divide Taiwan Line sticker users into three clusters by their profiles and then find each group's social media utilization and online purchase behaviors for investigating the Line sticker SMM and business models. Originality/value: This is the first study to offer a big data analytics to investigate and analyze the varieties in the use of Line sticker by exploring users' behaviors for further SMM and business model development.